The Role of Effective Leadership in Crisis Management: Study of Private Companies in Kurdistan - Kofand Anwar (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The main aim of the current study is to investigate the relationship between leadership styles and crisis management in private businesses. Leaders and managers of business corporations and large organizations permanently make crucial decisions and expect good results in achieving the objective that they have in mind. A quantitative technique used in order to analyses this study. 130 participants were involved in the present study. The researcher developed three main research hypotheses. The findings revealed that the highest value among all leadership styles was transformational leadership. A bigger sample size and including all the key races in Kurdistan would provide support for further studies.